PENGARUH PENGGUNAAN PC TABLET TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN INFORMATIKA DI SMP IT HAJI DJALALUDDIN BONJO ALAM KABUPATEN AGAM - Asmida Namora; Supriadi; Liza Efriyanti; Riri Okra (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research was motivated by the fact that some students have not yet achieved the minimum learning mastery in the Informatics subject, one of the contributing factors being the suboptimal use of technology such as PC Tablets during the learning process. The use of PC Tablets can be an engaging and interactive learning medium, but on the other hand, it can also cause distractions if not used wisely. Therefore, this study aims to determine the influence of PC Tablet usage on students' learning outcomes in the Informatics subject at SMP IT Haji Djalaluddin Bonjo Alam, Agam Regency. This research is a quantitative study using the ex post facto method. It involves two variables: the independent variable is the use of PC Tablets, and the dependent variable is the students' learning outcomes. Data were collected using an objective test instrument. The population consisted of 35 students, and the sample included 20 students, consisting of 9 students from grade VII and 11 students from grade VIII, selected using a saturated sampling technique. Based on data analysis and discussion, it was found that the average learning outcome of students with high PC Tablet usage was 81.09, while those with low usage had an average of 72.88. This indicates a positive correlation between the use of PC Tablets and improved learning outcomes. This result was supported by a simple linear regression test, showing an F-count of 23.085 with a significance value of 0.000 ≤ 0.05, indicating that H₀ is rejected and H₁ is accepted. Furthermore, the coefficient of determination (R²) was 0.5615 or 56.15%, showing that PC Tablet usage contributes 56.15% to the variation in students’ learning outcomes, while the remaining 43.85% is influenced by other factors. Thus, it can be concluded that there is a significant influence of PC Tablet usage on students' learning outcomes in the Informatics subject at SMP IT Haji Djalaluddin Bonjo Alam, Agam Regen